Different Modalities In The Management Of Ocular Surface Squamous Neoplasia (Indian Journal of Applied-Basic Medical Sciences, 2022)
Purpose: To study the different modalities in the management of Ocular Surface Squamous  Neoplasia(OSSN). Method: A prospective study of 30 cases of OSSN was undertaken. Based on patient factors and  tumour size and characteristics , 20 patients underwent surgical excision with cryotherapy and 10  patients were managed conservatively with topical interferon therapy. Patients were followed up for a  period of nine months. Results: OSSN is more common in males (80%) with mean age of 55 years (range 30-76 years).  Histopathology report of excision biopsy showed 6 benign dysplasia, 8 carcinoma in situ and 6  invasive squamous carcinoma. Postoperative topical interferon reduced the risk of recurrence. Of the patients who underwent interferon therapy, complete resolution was seen in 6 cases. Conclusion : Management of OSSN requires adequate excision and regular follow up to monitor any  recurrence. Although surgical excision is still the gold standard for OSSN treatment, topical  interferon has revolutionised the management of OSSN. Pre and Post operative adjunctive therapy  should be considered to prevent recurrence.
Keywords: ocular surface squamous neoplasia(OSSN); modality of management; result